Peran Tokoh Adat dalam Penyelesaian Konflik Hak Ulayat Tanah Adat di Desa Partungko Naginjang - Lestari Lumban Batu; Sri Hadiningrum; Windawati Pinem; Parlaungan G. Siahaan; Ramsul Nababan (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aims to examine the nature of conflicts over the management of customary land in Partungko Naginjang Village, Harian Subdistrict, Samosir Regency. The study focuses on determining the status of customary land, the causes of conflicts over its management, and the factors hindering conflict resolution in Partungko Naginjang Village. The research method employed by the author in this study is a qualitative descriptive approach. This study was conducted in Partungko Naginjang Village. Two types of data sources were used: primary data, which was collected directly in the field, and secondary data, which was obtained from books, journal articles, and official documents related to the research issue. Data collection techniques included observation, in-depth interviews, and documentation. The results of the study indicate that traditional leaders play a crucial role as mediators in resolving conflicts over customary land rights through traditional deliberations grounded in the Dalihan Na Tolu principle. They do this by tracing the root causes of the problem, bringing the conflicting parties together, and formalizing the agreement in a written contract without involving the formal legal system. However, traditional leaders face a number of obstacles, including third-party interference, selfishness, and the community’s limited knowledge of the history of customary lands; a lack of coordination with village officials; limited authority in conflicts with criminal elements; and a low level of community willingness to compromise during deliberations.